Treatment of amanita phalloides intoxication. A report of 3 cases and review of the literature - (:unkn) unknown (My University, 1991)
Mushroom poisoning is associated with high mortality rate and is not uncommon in many countries. Two of 3 pediatric patients who had eaten mushrooms developed signs and symptoms of poisoning and were treated with hemodialysis while the other patient only received conservative therapy. Forced diuresis and chemotherapy with or without hemodialysis were found effective in improving clinical and laboratory abnormalities. Combination of recently advanced techniques with conservative therapy in addition to early diagnosis of mushroom poisoning may significantly reduce the high mortality rate. Pathogenesis, management and treatment of amanita phalloides intoxication are discussed in this paper.